Ethnoecology behavioral of Southern Right Whale Eubalaena australis (Desmoulins, 1822) through the local ecological knowledge of artisanal fishermen in Southern Right Whale Area of Environmental Protection, southern Brazil - Zappes, Camilah Antunes; Danielski, Mônica Lauriano; Di Beneditto, Ana Paula Madeira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The aim of this study is to characterize the local knowledge displayed by the fishermen at Garopaba Municipality, Santa Catarina state, Brazil, regarding the behavior of Southern Right Whale, Eubalaena australis, in the region of the Southern Right Whale Area of Environmental Protection (AEP). In October of 2010 there were performed 33 interviews with local fishermen and found that 81.8% (n = 27) of the interviewed were able to identify the species by its area of occurrence, coloration, and body size. The analyses were based on interviews of 27 selected fishermen. Were described 10 common behavioral ethnocategories adults and infants, in which the most frequent was ‘do nothing’ to vessels (n = 13; 26.0%). For the specific behaviors of the adult were described 25 ethnocategories (n = 72) and the most frequent was ‘playing’ (n = 13, 18.1%). Four ethnocategories been described for infants (n = 18) and are relate to feeding/breastfeeding (n = 15, 83.3%) and the calling/interaction events with the adult female (n = 3, 16.7%). From the empirical offered by artisanal fishing, the interviewed were able to recognize the species, to distinguish between adults and infants and to describe its main behavioral characteristics.